PENGARUH KOMPENSASI DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI (Studi Empirik terhadap Pegawai Tetap dan Kontrak pada Perusahaan Menengah dan Besar di Kota Palembang) - Zunaidah zunaidah (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2010)
The phenomenon of this research is about the paradigm of change that some enterprises employed both the permanent and contractual employees to improve an efficiency of organization goals. The objective of this research are to describe compensation, job characteristic, leadership, job satisfaction and job performance; to know and examine the influence of compensation, job characteristic, and leadership on job satisfaction and job performance for permanent and contractual employees of medium and large enterprises in Palembang City.The kind of this research is survey verification on 482 respondents of 100 medium and large enterprises in Palembang City. Methods of sampling used in this research were stratified random sampling and simple random sampling. Data are analyzed using descriptive and quantitative analysis by applying the method of Structural Equation Model (SEM) and using Linear Structural Relationship (LISREL) program.Some results could be identified that the description of compensation, job characteristic, leadership, job satisfaction and job performance were important to permanent and also contractual employees which required between the mild and high categories. The results of quantitative analysis by testing of hypothesis shown that the influenced of compensation, job characteristic, and leadership on job satisfaction and job performance were positive and significant. The influenced of job satisfaction on job performance was significant. The influenced of compensation, job characteristic, leadership, and job satisfaction on job performance were statistically positive and significant of permanent and also contractual employees of medium and large enterprises in Palembang City.Keywords: Compensation, job characteristic, leadership, job satisfaction, job performance, permanent and contractual employees.